1981
DOI: 10.1017/s0043174500040327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pre-Irrigation Period on the Activity of Ethofumesate Applied to Dry Soil

Abstract: Applications of ethofumesate [(±)-2-ethoxy-2,3-dihydro-3,3-dimethyl-5-benzofuranyl methanesulfonate] at rates from 0.3 to 1.4 kg/ha were made in the field to soils of 2 and 30% (w/w) soil moisture. After 2 to 4 days, all soils were irrigated to establish stands of either sweet corn (Zea maysL. ‘Jubilee’) or winter wheat (Triticum aestivumL. ‘Stephens’) used as bioassay species for ethofumesate activity. Ethofumesate, at most rates, was significantly less effective on both corn and wheat when applied to dry soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…These data support previous work (9) which indicated that chemical degradation was the likely mechanism for loss of ethofumesate activity when ethofumesate was ap plied to dry soils in the field. Some increase in the quantity of tightly adsorbed herbicide also occurred, and this ad sorption likely combined with the degradation process to reduce activity.…”
Section: C-compoundsupporting
confidence: 91%
See 1 more Smart Citation
“…These data support previous work (9) which indicated that chemical degradation was the likely mechanism for loss of ethofumesate activity when ethofumesate was ap plied to dry soils in the field. Some increase in the quantity of tightly adsorbed herbicide also occurred, and this ad sorption likely combined with the degradation process to reduce activity.…”
Section: C-compoundsupporting
confidence: 91%
“…The activity of ethofumesate decreased when applied to a dry soil (wetted 2 to 4 days later) compared to a wet soil (9). Preliminary laboratory studies suggested that increased ethofumesate degradation in dry soil was the most likely mechanism for activity loss; however, changes in the manner and extent of adsorption could not be eliminated as a possible mechanism for the activity loss.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, mechanical incorporation is often required to activate ethofumesate to achieve consistent weed control (Entz 1982). Additionally, McAuliffe and Appleby (1981) reported significant chemical degradation losses when ethofumesate was applied directly to the surface of dry soils without an activating precipitation event or irrigation event within 4 d of application.…”
Section: Introductionmentioning
confidence: 99%
“…McAuliffe and Appleby ( , ) found greater herbicidal activity on wet soils than on dry soils, suggesting another mode of ethofumesate dissipation. In the present study, faster dissipation was observed in thatch than in the 0−1 cm soil layer of the bare soil plots.…”
Section: Discussionmentioning
confidence: 97%